Using the Quizizz Application to Increase Student Interest, Concentration and Learning Outcomes in Class XI Agribusiness, Food Crops and Horticulture at SMK Negeri 1 Mamasa - Arruan, Yernalia; Rais, Muhammad; Mukhlis, Andi Muhammad Akram (PT FORMOSA CENDEKIA GLOBAL, 2024)
Improving learning outcomes, student interest in learning, and learning concentration are the objectives of classroom action research at SMK Negeri 1 Mamasa class XI ATPH. Each research cycle consists of two cycles, namely planning, implementation, observation and reflection. Students' interest and focus when using the Quizzizz application during the learning process is measured through administering student questionnaires. Evaluating student educational outcomes is one method for determining short-term learning outcomes. We can conclude that improving learning outcomes in class with the Quizzizz application, interest and focus of students at SMKN 1 Mamasa class XI ATPH, based on research data collected through questionnaires and pre and post tests.